2013
DOI: 10.1186/1475-2875-12-431
|View full text |Cite
|
Sign up to set email alerts
|

In vitro piperaquine susceptibility is not associated with the Plasmodium falciparum chloroquine resistance transporter gene

Abstract: BackgroundDihydroartemisinin-piperaquine is a new ACT that is administered as single daily dose for three days and has been demonstrated to be tolerated and highly effective for the treatment of uncomplicated Plasmodium falciparum malaria. Piperaquine was used alone to replace chloroquine as the first-line treatment for uncomplicated malaria in China in response to increasing chloroquine resistance in the 1970s. However, the rapid emergence of piperaquine-resistant strains that resulted in the cessation of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…3) (36). Interestingly, consistent with prior reports (7,37), the associations seen for other aminoquinolines were not seen for piperaquine. Associations with other polymorphisms and for other drugs were mostly not significant.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3) (36). Interestingly, consistent with prior reports (7,37), the associations seen for other aminoquinolines were not seen for piperaquine. Associations with other polymorphisms and for other drugs were mostly not significant.…”
Section: Resultssupporting
confidence: 91%
“…Third, we Associations of ex vivo drug sensitivity with transporter polymorphisms. We and others have previously shown that polymorphisms in the putative transporters pfcrt and pfmdr1 are associated with altered ex vivo drug sensitivity (7,12,(34)(35)(36)(37)(38). We tested for associations between pfcrt K76T and pfmdr1 N86Y, Y184F, and D1246Y polymorphisms, and the ex vivo drug sensitivities were determined for samples collected in 2016 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, China-Myanmar border isolates with a single Pfmdr1 copy and the Pfcrt K76T genotype were reported to have reduced CQ and PPQ susceptibility (38). While there appears to be a link between PPQ and CQ resistance, PPQ may have additional resistance mechanisms suggested by preserved activity against CQ-resistant isolates from Africa (41,42) and lack of correlation between Pfcrt polymorphisms and reduced PPQ susceptibility in isolates from various regions (43,44). Our findings support the notion that until definitive molecular markers of PPQ clinical resistance are identified, the combination of Pfmdr1 deamplification and PPQ IC 50 s is useful for tracking what appears to be rapidly emerging PPQ resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, PPQ comprises two CQ-like 4-aminoquinoline moieties with a central linker. This drug is generally effective against parasites that evolved resistance to CQ through specific sets of point mutations in the P. falciparum CQ resistance transporter (PfCRT), which is also present on the digestive vacuole membrane 34,35 (Fig. 2 and Box 1).…”
Section: Multidrug Resistance (Mdr)mentioning
confidence: 99%